A decade of Shifting Trends, Themes, and Trajectories in Linguistics Studies - Yaqin, Lalu Nurul (Proceeding International Conference on Malay Identity, 2024)
The trend topics plot identifies emerging and popular research areas over the years, with a clear rise in themes related to Computational Linguistics, machine learning, language models, and natural language processing. The USA, China, and the United Kingdom are leading in contributions, with significant publications in journals like "Transactions of the Association for Computational Linguistics" and "Computational Linguistics." It highlights the central themes, emerging trends, and the global distribution of research efforts. This information can guide researchers, institutions, and policymakers in making informed decisions about future research directions, collaborations, and funding allocations. The visualizations effectively capture the complexity and dynamics of the field, showcasing the interconnectedness and evolution of various research themes over time in linguistics studies.